DAMPAK PENAMBANG PASIR TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT DI SEPANJANG BATANG SUMPUR NAGARI PADANG GELUGUR KECAMATAN PADANG GELUGUR KABUPETEN PASAMAN - KHOFIFAH, NUR; Iskarni, Paus (JURNAL BUANA, 2025)
The research aims to analyze the impact of sand mining on income, food needs, family education, health, and housing conditions in Nagari Padang Gelugur. This research is a quantitative descriptive study using a simple random sampling method. The respondents in this research were 51 workers. The research results are: (1) Average income of sand miners in Nagari Padang Gelugur previously amounted to. IDR 80,176 per day with an average monthly of IDR 1,882,696, after mining is IDR. 96,470 per day and a monthly average of IDR 2,794,617. (2) Condition the food needs of the sandminers workers is eat 2-3 times a day, the daily needs including satisfied (3) Level of education family of the Sandminers including improved proved with the children of sandminers able to pursue education. (4) Health condition of the workers they don’t consume vitamins and average medicinal allowance they use BPJS (5) Condition of house sandminer workers as many as 27 people (52.9%) have been able to do renovation of their home.